Primary chronic septic endocarditis as an alternative to acute rheumatic fever - the obligate component of the multicomponent noncyclic pandemic of the 21st Century - GM Bushmanova; MV Supotnitskiy; BV Churin (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
The concepts of acute rheumatic fever [1-3] and septic endocarditis (according to the International Classification of Diseases, is called infectious endocarditis. Septic endocarditis is the principal author's standpoint) - diseases that are still considered the main causes of acquired heart defects in Russia, have been under discussion for many years. The main question pertaining to this is the "specificity" of its pathogen. The opinion about the strict nosological independence of diseases, established in the late 60s, was questioned in the early 80s.